Literatura obozowa. Wstęp - Morawiec, Arkadiusz (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
The article contains terminological considerations concerning the term ‘camp literature’. In Polish literary studies it is most often referred to literature dealing with German Nazi camps, in particular concentration camps and death camps, and, less frequently, Soviet camps, especially forced labor camps. However, this definition turns out to be too narrow. It should also include the lesser-known works of Polish literature concerning, among others, the Polish internment camp (concentration camp) in Bereza Kartuska, communist labor camps set up in postwar Poland and the Spanish (Francoist) concentration camp in Miranda de Ebro. The term ‘camp literature’ could also include works on internment camps, prisoner camps, and even ghettos. The camp literaturę (not only Polish writings) requires, what is very important, a comparative approach.